Patients' perception of differences in general practitioners' attitudes toward immigrants compared to the general population: Qualicopc Slovenia - Jakič Maja; Rotar Pavlič Danica (Sciendo, 2016)
Globally, the number of immigrants is rising every year, so that the number of immigrants worldwide is estimated at 200 million. In Slovenia, immigrants comprise 6.5% of the overall population. Immigrants bring along to a foreign country their cultural differences and these differences can affect immigrants' overall health status and lead to chronic health conditions. The aim of this study was to identify patients' perception of general practitioners' (GPs') attitudes toward immigrants in Slovenia.